Development of Integrated Natural Science Module With Local Content in Wetland Environment to Train Science Process Skills For 8th Grade Students of SMP N 23 Banjarmasin - Hendri Dwi Pangestu; Syubhan Annur; Arif Sholahuddin (Universitas Negeri Yogyakarta, 2020)
The result of observation and interview with science teacher at SMPN 23 Banjarmasin shows that students do not use any books when learning at class. The learning progress run by teacher centered while the students just listening and take a notes from teacher explanation. Students also never doing experimental learning in laboratory or in the field. The aim of this research is to describe about valitidy, practicality, and effectivity of the integrated natural science module with local content in wetland environment as media development for science learning. Population of this research is 8th grades students of SMPN 23 Banjarmasin. The method of this research is Research and Development (RnD) method using development design plot by Tessmer. The research indicates that the integrated science module has 81.25 value of validity which is shows the module are valid to use for learning media. The practicality of the module is 91.75 which indicates the module are easy to use bothly the teacher and student. The effectivity of the module calculated with N-gain which get value 0.71, it means the module are effective as learning media to reach learning purposes. The module also gain value 59.41 of science process skills indicates the module can help students to learn about science process skills.